Expressive Speech Acts and Public Sentiments in Netizen Responses to Political Posts on X - Darmawan, Asy Syams Wahyu; Degaf, Agwin; Anggrisia, Nur Fitria (JOLLT Journal of Languages and Language Teaching, 2025)
The rise of online platforms like "ð•" (formerly Twitter) has transformed political discourse, where netizens frequently use expressive speech acts to communicate emotions and opinions. This study examines how expressive speech acts are used in netizen comments responding to President Joe Biden’s post about U.S. economic growth, focusing on emotional expressions that reflect public sentiment. Through the application of Searle’s theory of speech acts and Austin’s felicity conditions, the research analyzes 46 comments using content analysis. The findings show a predominant use of literal and direct speech acts to express negative emotions, particularly dissatisfaction with Biden’s economic policies. Additionally, the presence of sarcasm and irony demonstrates the complexity of online discourse, where non-literal speech acts convey more nuanced forms of criticism. These insights emphasize the evolving role of digital communication in political engagement and suggest the need for further research on how speech acts shape public opinion.